Sustainability of the environmental culture, use and management of drinking water in the City of Huancayo - Viera-Peralta, Deybe E. (2019)
The general objective of the research was to determine the relationship between the sustainability of the environmental culture, use and management of drinking water in users - of the district of Huancayo. The theory behind the study is the theory of sustainable development. Due to the nature of the study, the type of research was basic, the level of research was descriptive - correlational, the methods were analysis, synthesis, observation and measurement; the design of the research was the non-experimental descriptive - correlational, the technique of gathering information was the survey, the instrument was the survey questionnaire, the population was made up of 920 families, the sample was 272 families. The results according to the processing of the data showed that 64.3% of the families consider that the environmental culture of the families is bad and 57.8% consider that the use and management of the water of the families is bad; To test the general hypothesis, we used the correlation coefficient calculated between the variable environmental culture and the variable use and management of drinking water, determining the direct link according to chi-square 319,793, and with 16 gl, it can be noted that the value of significance is less than the value of p (0.000 <= 0.05), it was concluded that the environmental culture is favorably related to the use and management of the drinking water in users of the district of Huancayo.